Role of training programs approved by the Iraqi Athletics Federation on the performance of Iraqi coaches - Ebadi Alkhafaji, Sajad Mohammad; Mirzazadeh, Zahrasadat; Talebpour, Mahdi; Keshtidar, Mohammad; Abadi Abed, Mohamed (SPORT TK-EuroAmerican Journal of Sport Sciences, 2022)
The purpose of this study was to investigate the role of training programs approved by the Athletics Federation on the performance of coaches in Iraq and also to develop a model for evaluating the performance of athletic coaches. A cross-sectional study was carried out. A total of 60 experts from the Athletics Federation participated in the study. To collect data, a modified questionnaire by Mohammadi (2016) was used. The face and content validity of the questionnaire was confirmed by sports management professors and its reliability was higher than 0.7. In order to analyze the research data, the Statistical Package for the Social Sciences (SPSS version 22) was used, and to perform structural equations and model presentation the AMOS software was used. Based on the results of the exploratory factor analysis, eight factors were identified, which in order of priority included technical skills, management skills, classroom teaching techniques, motivational skills, individual and moral characteristics, sport characteristics and work experience, emotional and human characteristics and social characteristics. Also, the results of the structural equation modeling test showed that all factors were statistically significant (p = 0.001) and the research model had a good fit. Regarding the results of the research, it was concluded that for coaches to perform more successful, technical and management skills should be given more importance than other factors. The role of athletics programs in training coaches is also very important. Therefore, developing the capabilities of coaches is not possible without using a system of monitoring and evaluating performance.